A New Type of Ser Substitution for γ Arg-275 in Fibrinogen Kamogawa I Characterized by Impaired Fibrin Assembly - Mimuro, Jun; Kawata, Yoichi; Niwa, Kazuki; Muramatsu, Shin-ichi; Madoiwa, Seiji; Takano, Hiroshi; Sugo, Teruko; Sakata, Yoichi; Sugimoto, Tomoyoshi; Nose, Koichiro; Matsuda, Michio (Thrombosis and Haemostasis, 1999)
A new type of substitution, Arg to Ser at γ275, has been found in a heterozygous dysfibrinogen derived from a 23-year-old woman with no major bleeding or thrombosis. By sequence analyses of the affected γ-chain and its gene, we found a single amino acid substitution of γ Arg-275 to Ser in an aberrant γ (274-302) residue peptide isolated from lysyl endopeptidase-digests of the patient’s fibrinogen. In agreement with this amino acid substitution, we identified a single nucleotide exchange of A for C at position 5728 in the γ-chain gene creating a codon (AGC) encoding Ser instead of the codon (CGC) encoding Arg at position γ 275. Like two other known types of mutants with a His or Cys substitution at this position, the functional abnormality was characterized by delayed fibrin polymerization, most likely due to impaired abutting of two D domains of adjacent fibrin monomers in the same strand of fibrin protofibrils. The structural derangement that affects the D:D association may not be so severe as compared with those of Cys and His mutants, possessing an additional disulfide-linked Cys molecule and an imidazole ring at the mutation site, respectively.